Are high lags of accommodation in myopic children due to motor deficits?. (January 2017) - Labhishetty, Vivek; Bobier, William R.
Highlights: Blur accommodation but not convergence accommodation (CA/C) is reduced in myopes. Myopes show a similar rate of change in the response dynamics like the emmetropes. Atypical response patterns exist with blur accommodation but decrease with age. Pure sensory or motor deficit doesn't predict the abnormal behavior in myopes. Model simulation with altered sensory and motor gain predicts the myopic behavior. Abstract: Children with a progressing myopia exhibit an abnormal pattern of high accommodative lags coupled with high accommodative convergence (AC/A) and high accommodative adaptation. This is not predicted by the current models of accommodation and vergence. Reduced accommodative plant gain and reduced sensitivity to blur have been suggested as potential causes for this abnormal behavior. These etiologies were tested by altering parameters (sensory, controller and plant gains) in the Simulink model of accommodation. Predictions were then compared to the static and dynamic blur accommodation (BA) measures taken using a Badal optical system on 12 children (6 emmetropes and 6 myopes, 8–13 years) and 6 adults (20–35 years). Other critical parameters such as CA/C, AC/A, and accommodative adaptation were also measured. Usable BA responses were classified as either typical or atypical. Typical accommodation data confirmed the abnormal pattern of myopia along with an unchanged CA/C. Main sequence relationship remained invariant between myopic and nonmyopic children. An overall reduction was noted in the response dynamics such as peak velocity and acceleration with age. Neither a reduced plant gain nor reduced blur sensitivity could predict the abnormal accommodative behavior. A model adjustment reflecting a reduced accommodative sensory gain (ASG) coupled with an increased AC cross-link gain and reduced vergence adaptive gain does predict the empirical findings. Empirical measures also showed a greater frequency of errors in accommodative response generation (atypical responses) in both myopic and control children compared to adults.